Peran generasi z sebagai penggerak dalam mengubah budaya anti korupsi di Indonesia melalui media digital - Khairunnisa, Amelia Zulfa (Maliki Interdisciplinary Journal, 2026)
Corruption remains one of the major obstacles to Indonesia’s national development. Efforts to eradicate corruption cannot rely solely on law enforcement but also require preventive approaches through anti-corruption education. In this context, Generation Z holds a strategic position as an agent of change because they grow alongside digital technology and actively use social media in their daily lives. This article aims to analyze the role of Generation Z as a driving force in building an anti-corruption culture in Indonesia through digital media. This study uses a qualitative method with a literature study approach by reviewing various journals, books, and relevant scientific articles. The findings show that digital media such as Instagram, TikTok, YouTube, podcasts, and online webinars can serve as effective tools for anti-corruption education through social campaigns, information dissemination, and public oversight. However, the rapid growth of digital media also presents challenges, including low digital literacy, the spread of misinformation, and the normalization of dishonest behavior on social media. Therefore, strengthening character education, digital literacy, and collaboration among families, educational institutions, government, and society is necessary to build a culture of integrity. Generation Z has great potential to become a driving force for social change toward a more transparent and corruption-free Indonesia.